BEST-FIT COSMOLOGICAL PARAMETERS FROM OBSERVATIONS OF THE LARGE SCALE STRUCTURE OF THE UNIVERSE - Novosyadlyj, B.; Apunevych, S.; Durrer, R.; Gottloeber, S.; Lukash, V. (Одеські астрономічні публікації, 2017)
The possibility to determine cosmological parameters on the basis of a wide set of observational data including the Abell-ACO cluster power spectrum and mass function, peculiar velocities of galaxies, the distribution of Ly-α clouds and CMB temperature fluctuations is analyzed. Assuming a flat universe, ΩΛ + Ωm= 1, with purely scalar perturbations, we show that a χ2 minimization method applied on this data set determines quite precisely the values of the spectral index n of the primordial power spectrum, the baryon and massive neutrino density Ω b and Ω v respectively, the Hubble constant h ≡ H0/(100km / s / Mpc) and the value of the cosmological constant, ΩΛ. Varying all parameters we find that a tilted ΛMDM model with one species of massive neutrinos and the parameters n = 1.13 ± 0.10, Ωm = 0.41 ± 0.11, Ω v = 0.06 ± 0.028, Ωb = 0.039 ± 0.014 and h = 0.70 ± 0.12 matches the observational data best.